EVALUASI KESESUAIAN “BEBERAPA JENIS TANAMAN” DALAM SISTEM WANATANI DI WILAYAH DESA NGADIPIRO KECAMATAN NGUNTORONADI KABUPATEN WONOGIRI - Joko Winarno; Yogi Rachmadhika; Supriyadi Supriyadi (Faculty of Agriculture, Universitas Sebelas Maret, 2010)
Title : Evaluation “Appropriatness of Some Kinds of plant” in The System of Agroforestry in The Area Ngadipiro, Nguntoronadi, Wonogiri. The research was conducted in July 2008 until October 2008, in Ngadipiro, Nguntoronadi, Wonogiri. The research is aimed to evaluated the appropriateness of the plant teak, cashew fruit, melinjo, ground nut and grass the setaria as a part in the agroforestry system in Ngadipiro, Nguntoronadi, Wonogiri and to give some kind of agroforestry planting pattern model among teak, cashew fruit, melinjo, ground nut and grass the setaria in Ngadipiro, Nguntoronadi, Wonogiri. The research is fenomological qualitative description research it means that the research takes the data from the field which is supported by quantitative analysis in laboratory. Set of analysis in the research is set of field map and the soil sample taking technique is purposive sampling method. While, to know the field appropriateness class, the research compares the quality and the field characteristic with the plant growing condition from PPT Bogor 2003. The planting pattern model is based or plant functions and according to planting pattern model proposal from PPLH 2008. To know assess the egibility of is effort farmer the researcher does the B/C ratio analysis and studies plant use value. The result of the research shows that the appropriateness of teak, cashew fruit, melinjo, ground nut and grass the setaria in Ngadipiro is around S3 to N (marginal appropriate to inappropriate). There are three planting pattern model which can be used to lessening level of erosion danger in Ngadipiro. They are Model A (The mix of teak, cashew fruit, ground nut and grass the setaria), Model B (The mix of teak, melinjo, ground nut and grass the setaria) and Model C (The mix of teak cashew fruit, melinjo, ground nut and grass the setaria) While from the B/C ratio analysis and assess the egibility of is effort farmer which based on the use of the plant shows that of teak, cashew fruit, melinjo, ground nut and grass the setaria is appropriate to be tried and to be developed in the research field in Ngadipiro. Keywords: agroforestry, plant approprianteness, planting pattern